HUMAN CAPITAL DEVELOPMENT THROUGH INVESTMENT: INTERNATIONAL EXPERIENCE OF DEVELOPING COUNTRIES (Marketing Journal, 2025)
This article examines the role and importance of human capital in the formation and development of a country’s economy. It analyzes the impact of investments in education, healthcare, and innovation on sustainable growth, with a particular focus on develop ing countries. The paper also presents comparative information on the share of human capital in the national income of Uzbekistan and selected developed countries. Based on international experience, the study highlights effective strategies —such as promoti ng circular migration, improving ICT skills, and strengthening gender equality —that can enhance the efficiency of human capital formation and its contribution to economic development.
Keywords: human capital formation; investment; developing countries; Uzbekistan; national income; education; healthcare; innovation; sustainable development